Nota sobre o emprego de EPTC no controle de ervas daninhas na cultura do feijão - C A da Silva, Telmo; Vieira, Clibas (Revista Ceres, 2024)
From preliminary studies on the use of the herbicide Eptam (EPTC) in the culture of bean (Phaseolus vulgaris L), the following conclusions were drawn: (1) doses of active ingredient up to and including 9 kg/ha did not cause injuries to the bean plants; (2) application of the herbicide eliminated the necessity of the first regular cultivation (normally two cultivations are made); and (3) 5 kg/ha, or perhaps less, of active ingredient of Eptam is suflicient for weed control.